Polysaccharides 2014
DOI: 10.1007/978-3-319-03751-6_52-1
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose from Lignocellulosic Waste

Abstract: Bioconversion of renewable lignocellulosic biomass to biofuel and value-added products is globally gaining significant importance. Lignocellulosic wastes are the most promising feedstock considering its great availability and low cost. Biomass conversion process involves mainly two steps: hydrolysis of cellulose in the lignocellulosic biomass to produce reducing sugars and fermentation of the sugars to ethanol and other bioproducts. However, sugars necessary for fermentation are trapped inside the recalcitrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 187 publications
(196 reference statements)
0
13
0
4
Order By: Relevance
“…Within hemicellulose, acetyl groups are the first to be hydrolyzed, followed by arabinan and xylan. This component (acetyl) of the side chains of the xylan backbone facilitates the autohydrolysis effect in LHW (Michelin et al, 2015).…”
Section: Chemical Composition Of Untreated and Lhw Pretreated Corncobmentioning
confidence: 99%
See 2 more Smart Citations
“…Within hemicellulose, acetyl groups are the first to be hydrolyzed, followed by arabinan and xylan. This component (acetyl) of the side chains of the xylan backbone facilitates the autohydrolysis effect in LHW (Michelin et al, 2015).…”
Section: Chemical Composition Of Untreated and Lhw Pretreated Corncobmentioning
confidence: 99%
“…Common wheat and spelt, barley, grain maize and corn-cob-mix accounted for a high share (86% in 2015) of the cereals produced in the EU-28 (EUROSTAT, 2017). These harvests generate a large amount of lignocellulosic residues that mainly consist of cellulose (30%-50%), hemicellulose (15%-35%) and lignin (10%-20%) that are linked with each other (Michelin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, lignocellulosic biomass has been considered a promising material for production of these enzymes because of its abundance, low cost and wide availability [6]. Besides, it has been shown that better performances are obtained when an enzyme complex is prepared from the same lignocellulosic material that is meant to be hydrolyzed by that complex [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Various types of lignocellulosic biomass, such as hardwood, bagasse, and straws, have been studied as inducer sources or fermentation substrate to improve the lignocellulosic enzyme production [10,11]. One of the ways to improve the production is to use pretreated biomass which can lead to an improvement in production and yield since the pretreatment breaks the lignocellulosic structure and makes cellulose and hemicellulose more accessible for the fermenting microorganisms [7,8]. Hydrothermal pretreatment, such as liquid hot water (LHW), has been considered a suitable and costeffective pretreatment for biomass fractionation.…”
Section: Introductionmentioning
confidence: 99%